2011
DOI: 10.1007/s13224-011-0055-2
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A H1N1 2009 (Swine Flu) and Pregnancy

Abstract: The Influenza A H1N1 pandemic (A H1N1) occurred between June 2009 and August 2010. Although the pandemic is now over, the virus has emerged as the predominant strain in the current seasonal influenza phase in the northern hemisphere. The A H1N1 influenza is a novel strain of the influenza A virus and is widely known as swine flu. The virus contains a mixture of genetic material from human, pig and bird flu virus. It is a new variety of flu which people have not had much immunity to. Much has been learnt from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 9 publications
1
31
1
Order By: Relevance
“…The patients with at least one of the foolowing symptoms or signs were defined as severe H1N1 infection; persistant fever (>38 0 C) for at least 3 days, nausea, vomitting, diarrhea, dehydration, chest pain and productive coughing, (Table I, Table II (8,9) . Although the H1N1 influenza virus infection lasted 7 days in immunocompetent human, it was complicated with secondary viral or bacterial pneomonia in high risk groups (such as; health care professionals, patients with chronic illness, diabetics, morbid obese patients and pregnants) (1,8,10) .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The patients with at least one of the foolowing symptoms or signs were defined as severe H1N1 infection; persistant fever (>38 0 C) for at least 3 days, nausea, vomitting, diarrhea, dehydration, chest pain and productive coughing, (Table I, Table II (8,9) . Although the H1N1 influenza virus infection lasted 7 days in immunocompetent human, it was complicated with secondary viral or bacterial pneomonia in high risk groups (such as; health care professionals, patients with chronic illness, diabetics, morbid obese patients and pregnants) (1,8,10) .…”
Section: Methodsmentioning
confidence: 99%
“…Both the need for ICU and mortality rates were increased if the patients had dyspnea, tachpnea (>30/min), tachycardia, pneumonia, loss of conciousness and need oxygen supply during admission (1) . Studies reported that the rate of ICU requirement among pregnant women were between 7 to 9% (10,13) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations